Early adoption of the tropical forage legume Arachis pintoi in Huetar Norte, Costa Rica - Wunscher, T.; Schultze-Kraft, Rainer; Peters, Michael; Rivas Ríos, Libardo (Cambridge University Press, 2004)
The legume Arachis pintoi has a number of characteristics which enable it to make a valuable contribution to the development of sustainable and productive pastures in the tropics. It was introduced to Costa Rica for this reason, in 1987. The objective of this study was to analyse the adoption of A. pintoi as a forage legume in Huetar Norte, a region in the north of Costa Rica. The adoption process was analysed to identify the contributory factors and to make recommendations for measures which could be taken to promote the process. To collect the data, 115 randomly selected livestock holders and an additional 34 farmers known to have planted A. pintoi were interviewed. Farmers see improved pastures to be the most important technology to enhance forage and cattle production. It was confirmed that A. pintoi is a potential improved pasture alternative. Although A. pintoi was well known., the adoption rate was low. Lack of availability of seed, technical assistance and information about the use and management of A. pintoi hinder adoption. Difficulties in establishment and maintenance were also recorded.